2001
DOI: 10.1051/0004-6361:20010221
|View full text |Cite
|
Sign up to set email alerts
|

HD 152248: Evidence for a colliding wind interaction

Abstract: Abstract. We present the results of a four year spectroscopic campaign on the early-type binary system HD 152248. Our analysis yields a new classification as O7.5III(f) + O7III(f), in contradiction with previous classifications of the components as supergiants. We derive improved orbital elements and the corresponding masses (M1 = 29.6 M and M2 = 29.9 M ) are somewhat larger than previously reported in the literature, although they are still significantly lower than the ones expected from evolutionary tracks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 28 publications
4
74
1
Order By: Relevance
“…We calculated the geometrical center of the massive MS members with masses greater than about 5 M (V ≈ 11 mag) and adopted this as the center of NGC 6231. The adopted center of NGC 6231 is α J2000 = 16 h 54 m 11. s 7, δ J2000 = −41 • 50 20 , which is approximately equidistance from HD 152248 (O7.5III+O7III(f), Sana et al 2001); HD 152249 (O9Ib(f), Sana et al 2008) and HD 152270 (WC7+O6V, Hill et al 2000).…”
Section: Surface Density Profiles and The Radius Of Ngc 6231mentioning
confidence: 88%
“…We calculated the geometrical center of the massive MS members with masses greater than about 5 M (V ≈ 11 mag) and adopted this as the center of NGC 6231. The adopted center of NGC 6231 is α J2000 = 16 h 54 m 11. s 7, δ J2000 = −41 • 50 20 , which is approximately equidistance from HD 152248 (O7.5III+O7III(f), Sana et al 2001); HD 152249 (O9Ib(f), Sana et al 2008) and HD 152270 (WC7+O6V, Hill et al 2000).…”
Section: Surface Density Profiles and The Radius Of Ngc 6231mentioning
confidence: 88%
“…Sana et al 2001). Various physical effects can induce a S-S signature: gaseous streams in the systems, ellipsoidal variations, surface streams, and changes in the local surface temperature due to, e.g., mutual illumination or heating from a wind-wind collision (e.g., Bagnuolo et al 1999;Linder et al 2007).…”
Section: H Sana and C J Evansmentioning
confidence: 99%
“…We note however, that the available light curve solution of HD 152248 (Mayer et al 2001) does not support this idea. The present-day configuration of HD 152248 may have been affected by a past RLOF episode instead (Sana et al 2001). On the other hand, as stated previously the inclusion of rotation in the single star evolutionary models may in fact reduce the discrepancy between the observed and theoretical masses.…”
Section: Observational Evidence For Mass Exchange In Evolved Massive mentioning
confidence: 73%
“…In some cases, the comparison of the properties of their components with evolutionary tracks for single massive stars yields inconsistent results. For instance, in the case of HD 152248 (O7.5 III(f) + O7 III(f)) both stars appear overluminous for their masses (Sana et al 2001) and the evolutionary masses needed to account for the observed luminosity are ∼ 30% larger than the observed masses. Penny et al (1996) argued that this behaviour is an indication of ongoing Roche lobe overflow (RLOF).…”
Section: Observational Evidence For Mass Exchange In Evolved Massive mentioning
confidence: 99%